Parenting After Separation: Designing Legal Standards That Reduce Conflict, Not Just Resolve It - Fadhil Hayan Mochammad (Punggawa Law Review, 2026)
Post-separation parenting disputes often persisted despite final court orders because legal standards were commonly drafted to allocate parental time and authority rather than to govern the recurring coordination problems that generated repeat conflict. This article examined post-separation parenting as a governance challenge and assessed how legal standards could be designed to reduce conflict over time, not merely to resolve a single dispute. A doctrinal–normative analysis with a comparative policy lens was applied to identify where under-specified orders failed in practice, especially in schedules and handovers, shared decision-making, communication, and enforcement. The study developed a design framework that operationalized child-centred aims through mandatory minimum-content parenting plans, default rules for predictable flashpoints, defined decision domains with deadlock procedures, regulated communication protocols, and graduated enforcement that corrected minor breaches quickly while escalating responses for persistent non-compliance. The analysis also showed that cooperative models were unsafe or ineffective in high-conflict and high-risk families, requiring differentiated pathways such as parallel parenting and safety-sensitive restrictions. These findings supported a policy rubric for courts and legislators to draft standards that produced stability and reduced incentives for strategic obstruction.